A robust MOF-based trap with high-density active alkyl thiol for the super-efficient capture of mercury. Issue 86 (11th October 2019) - Yang, Pengfei; Shu, Yufang; Zhuang, Qixin; Li, Yongsheng; Gu, Jinlou
Abstract : A robust Zr-MSA MOF trap with high-density active alkyl thiol is successfully constructed for the super-efficient capture of mercury. Abstract : The first Zr-based metal–organic frameworks (MOFs) with high-density active alkyl thiol were successfully constructed in an aqueous phase. Thanks to the strong affinity between alkyl thiol and Hg 2+ ions, the robust MOFs feature high adsorption capacity (734 mg g −1 ), ultra-fast kinetics (removing 99.99% Hg 2+ in 5 min), super-high capture efficiency (dropping Hg 2+ concentration from 10 000 ppb to 0.11 ppb), wide working range of pH, high selectivity and good reusability.